PUBLIC VALUE PENGGUNAAN TRANSPORTASI UMUM KAI COMMUTER LINE JABODETABEK DI STASIUN MANGGARAI - Widiyanti, Anindita; Rostyaningsih, Dewi; Lituhayu, Dyah (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
DKI Jakarta is one of the cities with the highest level of congestion in Indonesia.The use of public transport, especially KRL, can be a solution to solvingcongestion problems. The use of KRL public transport is still found problems, soit has not been able to overcome congestion in DKI Jakarta. The existingproblems make public interest in using public transportation, especially KRL, notoptimal because of the many complaints felt by users, especially those that occurat Manggarai Station. This research aims to describe public values in the use ofpublic transport, especially KRL at Manggarai Station. By knowing public values,it is expected to help answer the problems that exist in the use of JabodetabekKRL public transport, especially at Manggarai Station. The method used is aqualitative approach, using Moore's (1995) theory of public value. Based on theresults obtained, the legitimacy dimension is quite good but there needs to bespecific rules regarding the maximum user limit on KRL. In the dimension ofoperational capability, the majority is good enough, but there needs to beimprovements in the aspects of assurance and responsiveness. The dimension ofsubstantial value (benefits) has also been felt by users who feel the benefits ofKRL transportation.